2023
DOI: 10.1039/d3ce00524k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of accumulated strain on fat bloom in CBS-based compound chocolates

Abstract: Understanding the phase behavior of cocoa butter substitute (CBS)-based compound chocolates is important for improving the deliciousness of confectionery products. This knowledge will help suppress fat blooms in CBS-based compound...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Any chocolate material or CB would intrinsically have lattice strain due to the mixture of cocoa solids, sugars, lecithin, and the mixture of TAGs, interrupting any chance of forming a perfect crystal lattice free of imperfections (interstitials, vacancies, dislocations, and layer faults) . It is for this reason a W–H analysis was done to estimate the relative differences in crystallite size and strain, and which has been applied recently by Koizumi et al in a CBS. The indexed W–H is applied here to gauge the effects of DMPC on chocolate crystal structure parameters using SAXS data as a fast method not convoluted by the complex diffraction pattern of sugar between 0.71 and 2.80 Q in wide-angle X-ray diffraction patterns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Any chocolate material or CB would intrinsically have lattice strain due to the mixture of cocoa solids, sugars, lecithin, and the mixture of TAGs, interrupting any chance of forming a perfect crystal lattice free of imperfections (interstitials, vacancies, dislocations, and layer faults) . It is for this reason a W–H analysis was done to estimate the relative differences in crystallite size and strain, and which has been applied recently by Koizumi et al in a CBS. The indexed W–H is applied here to gauge the effects of DMPC on chocolate crystal structure parameters using SAXS data as a fast method not convoluted by the complex diffraction pattern of sugar between 0.71 and 2.80 Q in wide-angle X-ray diffraction patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism which describes each type of fat bloom in chocolate is not fully known, and the focus on chocolate food-stuffs in research is to delay polymorphic transitions by modifying the kinetics. Small and wide-angle X-ray diffraction has been used to study microstrain on a cocoa butter substitute (CBS) which show accumulated strain in the preferred polymorph, β′ . The study demonstrated how accumulated strain can promote phase transitions and induce bloom in the CBS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal strain is a distortion of the fat crystal particles by the presence of foreign (non-TG) molecules [45]. In the case of the addition of the SE to PO, the assessment of strain is insurmountable, as the SE molecules might change the structure of TG lamellae.…”
Section: Crystal Strainmentioning
confidence: 99%
“…As such, the Williamson-Hall analysis consists of a line fitted through only two points, which is not ideal. Other authors include WAXS peaks; however, we believe that the q distance between the WAXS and SAXS peaks would distort the analysis even more [45]. Note: The authors would like to stress that applying the Williamson-Hall technique to a fat crystal network and its accompanying SAXS profile is not ideal.…”
Section: Appendix D Crystal Strain Assessments Of Po and Poementioning
confidence: 99%